Developing an epoxy composite dielectric with hollow carbon nanospheres - Sitole, Sophy (My University, 2020)
This dissertation presents the feasibility of developing an epoxy nanocomposite with hollow carbon nanospheres. The work entailed synthesis of the hollow carbon nanoparticles and then fabrication and characterisation of the epoxy nanodielectric. A template method with polystyrene nanoparticles as a prototype was used to synthesize the hollow carbon nanospheres (HCNs). The characterisation techniques which are scanning electron microscopy, transmission electron microscopy, Branauer Emmett-Teller, Raman spectroscopy and thermogravimetric analysis were used to confirm the chemical and physical properties of the synthesized HCNs. It was found that the synthesized HCNs have a relatively high surface area of 341.5 m²/g and an average diameter of 410±70 nm. A direct dispersion method incorporated with rheology analysis was used to fabricate the epoxy resin and nanodielectric material at different nanofiller loading levels. It was found that incorporating rheology analysis in the nanodielectric fabrication protocol can improve the efficiency of determining the optimal nanoparticle filler loading level for electrical tree endurance of the resultant nanodielectric. An electrical treeing test was used to characterise the fabricated nanodielectric material. A partial discharge measuring circuit according to the IEC 60270 was used to characterise the electrical trees grown in epoxy resin and nanocomposite material with either solid carbon nanospheres (SCNs) or HCNs. The performance of SCNs in epoxy of type araldite® FR476D and hardener® was used as a benchmark in comparing electrical tree endurance between SCNs/Epoxy and HCNs/Epoxy nanodielectric. It was found that HCNs improve the electrical insulation properties of epoxy but not to the same extent as the corresponding solid carbon nanospheres. This finding could be regarded as an indication that the electron scavenging properties of carbon nanoparticles (that has been reported in the literature) contributes to the superior properties of the carbon-based nanodielectrics. For the same particle size, solid carbon nanoparticles have more carbon content than mesoporous hollow carbon nanoparticles. Furthermore, there is a material type dependent compatibility relationship between nanoparticles and host material. Different types of epoxy showed different characteristics of the resultant nanodielectric for the same type of nanoparticle fillers
A dissertation submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Engineering, 2020